Circulation of Objects and Raw Material in the Atacama Desert, Northern Chile by the End of the Pleistocene. (2nd October 2019) - Herrera, Katherine A.; Pelegrin, Jacques; Gayo, Eugenia; Santoro, Calogero M.
ABSTRACT: About 13, 000 calendar years ago, the Atacama Desert (18–26°S) was occupied by some of the human groups who had begun to populate South America. The archaeological evidence from six sites located in Pampa del Tamarugal (PdT) it the hyperarid core of the Atacama Desert, including different objects and raw materials, shows a connection with different geographical areas within and outside PdT: (a) local circuits to acquire resources from the Pampa; (b) regional displacements that covered the coast and the Andes, more than 70 km away from PdT; and (c) displacements or interactions at a supra-regional level that connected PdT with the tropical and subtropical forests of South America, more than 600 km away. We propose a preliminary model for the local circuits that covers displacements from 40 minutes to 13 hours walking distance from residential locations to obtain fresh water, wood, rocks for knapping, and hunting activities.